2004
DOI: 10.1002/bse.410
|View full text |Cite
|
Sign up to set email alerts
|

Environmental upgrading of Third World enterprises through linkages to transnational corporations. Theoretical perspectives and preliminary evidence

Abstract: With economic globalization, Third World enterprises are increasingly collaborating with foreign firms through trade, subcontracting and equity linkages. The paper examines under which conditions linkages to foreign firms lead to environmental upgrading of Third World enterprises. Derived from the authors' research in a number of developing countries, the paper presents preliminary evidence of such upgrading. As the existing literature on environmental upgrading has a normative bias and tends to ignore economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 29 publications
3
71
0
1
Order By: Relevance
“…A 2006 report of the ministry of commerce confirmed this better CSR by MNEs in China, which were said to have an impact on Chinese companies as well (Wei, 2006), sometimes via supply chains (cf. Jeppesen and Hansen, 2004). An example that came to the fore after the empirical study had been concluded is Wal-Mart's announcement to convene a meeting for around 1,000 Chinese suppliers to help increase their environmental performance (Birchall, 2008).…”
Section: ==============mentioning
confidence: 99%
“…A 2006 report of the ministry of commerce confirmed this better CSR by MNEs in China, which were said to have an impact on Chinese companies as well (Wei, 2006), sometimes via supply chains (cf. Jeppesen and Hansen, 2004). An example that came to the fore after the empirical study had been concluded is Wal-Mart's announcement to convene a meeting for around 1,000 Chinese suppliers to help increase their environmental performance (Birchall, 2008).…”
Section: ==============mentioning
confidence: 99%
“…8.Green governance reforms: The environmental upgrading literature emphasizes the need for improvement in environmental performance beyond value chain upgrading (Jeppesen & Hansen, 2004). Accessing eco-innovation can help in solving environmental problems and gaining access to new technology for product and value chain upgrading in developing countries (Ockwell et al, 2010).…”
Section: Causal Conditionsmentioning
confidence: 99%
“…In addition, availability of environmental regulation, government support and forest sector policy (Bernauer, Engel, Kammerer, & Nogareda, 2006;Rennings, 2000); collaboration and interaction among institutions/actors;availability andacquisition of new technical knowledge; andpublic investment as well as market demand foster innovation processes in forestry (Kubeczko, Schaan & Anderson, 2002). Technical collaboration with foreign firms; monitoring and controlling; cross-functional collaboration and knowledge sharing; investment in new and clean technology; green skill development and training; development of a written environmental plan; development of environmental performance criteria; internal assessment of implementation of an environmental plan; implementation of certification and ISO 14001 standards; and extension of environmental criteria to the entire value chain are important processes for the adoption of greening practices (Darnall, Jolley, & Handfield, 2008;Jeppesen & Hansen, 2004). Existence of stakeholder dialogue and stakeholder knowledge integration, cultural and institutional development, public education, participatory environmental assessment and self-organization are key processes for changes in governing structures, efficient resource management, product stewardship and habitat preservation as well as for reducing pressure on natural resources (Berkes & Turner, 2006;Hart, 1995;Tabara & Pahl-Wastl, 2007).…”
Section: Causal Conditionsmentioning
confidence: 99%
“…Recent studies examine the transfer of knowledge and capabilities of MNEs (Gupta and Govindarajan,2000;Pèrez-Nordtvedt et al.2008;Fang et al, 2010). Jeppesen and Hansen (2004) summarized a number of approaches to developing countries enhancing the ability of their firms by building linkages with MNEs. First, the commodity chain approach indicates that products as a commodity is controlled through power balance between MNEs and developing countries.…”
Section: International Transfer Modelmentioning
confidence: 99%
“…The transfer of environmental management to developing countries will build first mover advantage to firms, and second, it in turn provides competitive advantage to suppliers as well (Jeppesen & Hansen, 2004). In contrast, the resource-based approach argues that resources and capabilities are the basis of growth and performance (Barney, 1991;Rugman & Verbeke, 1998).…”
Section: International Transfer Modelmentioning
confidence: 99%